1985
DOI: 10.1016/s0006-3495(85)83937-0
|View full text |Cite
|
Sign up to set email alerts
|

Laser Raman spectra of calf thymus chromatin and its constituents

Abstract: Extensive Raman measurements have been made on calf thymus chromatin, core chromatin, the (H3,H4)/DNA complex, and isolated DNA. The results indicate that the alpha-helical content of the nucleosomal histones gradually increases as they form the heterocomplexes that lead to the formation of the octameric nucleosome core. The secondary structure of the latter is not modified as it binds to DNA. The spectra indicate that the DNA essentially retains its B conformation in nucleosomes, although slight changes proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…It is clear therefore that the proteins in the nucleus possess predominantly ahelix and random coil domains. These findings are in accordance with Raman spectroscopic data obtained from isolated nucleosomes, nucleosome cores, and from isolated Calf Thymus and chicken erythrocyte chromatin containing little or no nonhistone proteins (NHP) (26)(27)(28). As demonstrated below NHP is abundantly present in the nuclei of granulocytes.…”
Section: -Sheet Signal Contributions Would Have Been Expectedsupporting
confidence: 90%
See 1 more Smart Citation
“…It is clear therefore that the proteins in the nucleus possess predominantly ahelix and random coil domains. These findings are in accordance with Raman spectroscopic data obtained from isolated nucleosomes, nucleosome cores, and from isolated Calf Thymus and chicken erythrocyte chromatin containing little or no nonhistone proteins (NHP) (26)(27)(28). As demonstrated below NHP is abundantly present in the nuclei of granulocytes.…”
Section: -Sheet Signal Contributions Would Have Been Expectedsupporting
confidence: 90%
“…The intensity of 1,094 cm-' DNA line is virtually insensitive to DNA-protein interactions in nucleosomes and chromatin (26)(27)(28) and in DNA-polylysine and DNA-polyarginine complexes (29,30). The intensity of 1,449 cm-' protein line is insensitive to protein secondary structure and depends only on the number of protein CH2 and CH3 groups (2,40).…”
Section: Determination Of Dna-protein Ratiomentioning
confidence: 99%
“…However, since no measurements were carried out at pH's lower than 1.8, this will not affect the general validity of the results presented here. The intensity of the 1094-cnr1 line is furthermore largely independent of the DNA-protein interactions that occur in nucleosomes and chromatin (Thomas et al, 1977;Hayashi et al, 1986;Savoie et al, 1985) and in DNA-polylysine complexes (Prescott et al, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in molecular structure lead to changes in the Raman spectrum. The technique has been widely applied to study the composition, structure, and interactions of nucleic acids and proteins (see, e.g., Erfurth & Peticolas, 1975; Goodwin & Brahms, 1978;Hayashi et al, 1986;Savoie et al, 1985;Thomas et al, 1977Thomas et al, , 1986. Measurements were made of chromosomes at low pH, chromosomes reneutralized after a brief incubation at low pH, and calf thymus DNA at low pH.…”
mentioning
confidence: 99%
“…An experiment (not shown) in which a mixture of glucose oxidase and catalase was added to a metaphase chromosome preparation showed that damage still occured. Such an enzyme mixture was shown [24] to be very effective in depleting a sample of free oxygen molecules. However, reactive hydrogen peroxide may be present and the enzymes contain tlavines which can act as sensitizers [23].…”
mentioning
confidence: 99%